A mutation in porcine pre-miR-15b alters the biogenesis of MiR-15b\16-1 cluster and strand selection of MiR-15b. - Wenyang Sun; Jing Lan; Lei Chen; Jinjie Qiu; Zonggang Luo; Mingzhou Li; Jinyong Wang; Jiugang Zhao; Tinghuan Zhang; Xi Long; Jie Chai; Zunqiang Yan; et al. (PLoS ONE)
MicroRNAs (miRNAs) are small non-coding RNAs that are involved in translational regulation of the messenger RNA molecules. Sequence variations in the genes encoding miRNAs could influence their biogenesis and function. MiR-15b plays an important role in cellular proliferation, apoptosis and the cell cycle. Here, we report the identification of a C58T mutation in porcine pre-miR-15b. Through in vitro and in vivo experiments, we determined that this mutation blocks the transition from pri-miRNA to pre-miRNA, alters the strand selection between miR-15b-5p and miR-15b-3p, and obstructs biogenesis of the downstream miR-16-1. These results serve to highlight the importance of miRNA mutations and their impacts on miRNA biogenesis.